2014
DOI: 10.1186/1742-2094-11-54
|View full text |Cite
|
Sign up to set email alerts
|

IVIg protects the 3xTg-AD mouse model of Alzheimer’s disease from memory deficit and Aβ pathology

Abstract: BackgroundIntravenous immunoglobulin (IVIg) is currently in clinical study for Alzheimer’s disease (AD). However, preclinical investigations are required to better understand AD-relevant outcomes of IVIg treatment and develop replacement therapies in case of unsustainable supply.MethodsWe investigated the effects of IVIg in the 3xTg-AD mouse model, which reproduces both Aβ and tau pathologies. Mice were injected twice weekly with 1.5 g/kg IVIg for 1 or 3 months.ResultsIVIg induced a modest but significant impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 68 publications
3
77
2
Order By: Relevance
“…Conflicting results have been published regarding IVIG's effects on NFTs in the 3xTgAD transgenic mouse model of AD, which develops both plaques and NFTs. Gammagard administration to these mice was reported to result in a small (~15%) but statistically significant decrease in hippocampal NFTs [17], but no reduction in tau pathology was found when Gamunex was administered [18]. These findings contrast with neuroprotective effects obtained when tauopathy mice were treated with monoclonal anti-pTau antibodies [6,7].…”
Section: Ivig1contrasting
confidence: 58%
“…Conflicting results have been published regarding IVIG's effects on NFTs in the 3xTgAD transgenic mouse model of AD, which develops both plaques and NFTs. Gammagard administration to these mice was reported to result in a small (~15%) but statistically significant decrease in hippocampal NFTs [17], but no reduction in tau pathology was found when Gamunex was administered [18]. These findings contrast with neuroprotective effects obtained when tauopathy mice were treated with monoclonal anti-pTau antibodies [6,7].…”
Section: Ivig1contrasting
confidence: 58%
“…No effect on synaptic proteins was observed either, including drebrin, whose levels are decreased in AD [69,70]. We previously reported that the drebrin loss in the brain cortex of 3xTg-AD was minimal compared to NonTg mice [35,46], while no difference was observed in synaptophysin and SNAP-25 levels between NonTg and 3xTg-AD mice [35,37,46]. In contrast, a previous study using a specific phenolic compound, resveratrol, already showed that APP/PS1 mice, another AD mouse model, demonstrated a 2.2-fold increase in drebrin when fed resveratrol [71].…”
Section: The Main Neuropathological Markers Of Ad Are Not Modified Bymentioning
confidence: 89%
“…Anxiety was assessed with the dark-light emergence test as previously described [39,46,47]. Animals were positioned in the dark compartment and the time spent in the illuminated compartment was measured for 5 min.…”
Section: Anxiety-like Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Some therapeutic strategies for AD attenuate synaptic dysfunction and improve cognitive behavior in AD models1718192021222324. Given the remarkable recovery of cognition in AD models of targeted-Aβ immunotherapy, it is necessary to determine the molecular correlations associated with improvement.…”
mentioning
confidence: 99%